Unikalumas ir entropija kultūros paveldo informacijoje ir komunikacijoje - Laužikas, Rimvydas (Information & Media, 2010)
XX amžiuje prasidėjusi informacinės ir komunikacinės paradigmų plėtra ir besiformuojanti tinklaveikos visuomenė neišvengiamai turi įtakos įvairių veiklos sričių, taip pat paveldo sampratai, paveldosaugos, paveldotvarkos ir paveldo informacijos bei komunikacijos procesams. Šio straipsnio objektas – informacinės ir komunikacinės paradigmų raiška paveldo erdvėje. Straipsnio tikslas – suformuluoti paveldo informacijos ir komunikacijos sampratą, parodant sąsajas su komunikacijos ir informacijos mokslų teorijomis bei pademonstruojant informacinės paradigmos taikymo paveldo tyrimuose galimybes. Straipsnyje pateikiami teoriniai svarstymai iliustruojami konkretaus paveldo objekto – Dubingių piliavietės archeologinių tyrimų pavyzdžiais.Straipsnyje pristatomo tyrimo metu nustatyta, kad paveldo informacijos ir komunikacijos požiūriu pagrįstuose tyrimuose galima tarpdiscipliniškai pritaikyti svarbiausias informacijos ir komunikacijos mokslų teorijas ir metodus. Jų taikymas paveldo erdvėje gali būti kreipiamas dviem lygiavertėmis tyrimų kryptimis: tyrimuose akcentuojant išskirtinius paveldo objektus ir artefaktus bei tyrimuose orientuojantis į masinės medžiagos pažinimą. Abi tyrimų kryptys leidžia kiekybiškai įvertinti paveldo objektus, nustatant paveldo kompleksų ir jų dalių santykį, lyginant paveldo objektus ir kompleksus, siekiant identifikuoti kompleksą sukūrusių visuomenių ypatumus.Pagrindiniai žodžiai: Paveldas, paveldo informacija ir komunikacija, informacijos teorija, komunikacijos teorija, komunikacijos ir informacijos mokslai, Dubingiai, archeologija, entropija.Uniqueness and Entropy in the Information and Communication on Cultural HeritageRimvydas LaužikasSummaryThe technologies that have been developing in the 20th–21st century gradually permeate all fields of human life and activities. These technologies open new opportunities for communication, management, information processing as well as for the development of new, based on the information and communication paradigms research methods, models of practical activities, and interdisciplinary research. In this context, it is promising to use the basic theories of communication and information science (McLuhan’s, Shannon’s, Lotman’s, Prigogine’s) and the definition of the communication and information on cultural heritage.The purpose of the article is to formulate the concept of information and communication regarding cultural heritage, to show links between heritage and information and communication science theories and the examples of using the information paradigm for heritage studies. The theoretical considerations are illustrated by examples from a particular heritage site – the Dubingiai (Moletai reg., Lithuania) castle site archaeological excavations.The concept of information and communication on cultural heritage is based on the definition of cultural heritage. If “cultural heritage – the entire corpus of material signs – either artistic or symbolic – handed on by the past to each culture…” (HEREIN…., 2009), then a single heritage object should be regarded as a sign (a minimum, indivisible, atomic information transmission unit) and the heritage complex as a text (medium, message). The signs and texts point to mental ideas and are part of a system applied by members of specific (past) culture for intercommunication. If we accept this definition, then heritage research means the decoding, i.e. “reading”the primary (archaeological complexes from past cultures) texts and the encoding, i.e. creating a secondary (scientifically for scientists) and tertiary (for general public) text in contemporary culture. Research of cultural heritage is the foundation for the further communicative use of the cultural heritage in our times (as museum exhibits, cultural monuments, etc.).This position allows customizing the quantitative parameters of information theory to the heritage research and extending the “toolbox” of heritage quantitative analysis. In this approach, a heritage complex as a text is an evolved, open (for external influence) and dissipative system. Such systems have all features of evolving systems determined by Ilya Prigogine (Prigogine, 2006): they evolve; their evolution is based on an objective arrow of time which ensures irreversibility of processes; the variability of system components, going on for a long time, causes changes in the whole system; the evolution of a system is a process that can be forecasted only in part; sometimes an evolving system experiences disturbances that change it essentially (system mutations); both systems evolve at a different speed; two systems the evolution of which started in different points of space and time, more and more recede from each other; two systems are not inter-integrating.In this way, we find two approaches to “reading the past”: a research of exclusive (unique) artifacts and research of mass artifacts. Both approaches say that unique (or mass) artifacts are markers of social structure, of trading connections, of urbanization, of cultural influences, etc. However, to use this method, we need statistically significant samples, the methodology of triangulation by several benchmark examples, and a relative scale of references. From the first point of view, perspective methods of “reading” the cultural heritage information are the content analysis and summaries of a complex information. In archaeology, it is the coefficient of graves with findings, the average number of unique finds in a grave, the average number of semantically valuable finds, the complex (text) density index, the complex readability index and mapping the network of finds on the basis of binary oppositions theory. From the second point of view, promising methods are information entropy modeling and calculation. The main problem of calculating entropy for heritage complexes is that the original text (the primary state of complex) is only hypothetical; it cannotbe reconstructed and it is problematical to record the entropy change. In this context, a productive way is the visualization and relative calculation of the general object-level entropy in the three-dimensional space-time model (X and Y as the geographical coordinates of archaeological object and Z as the chronological parameter). Also, the entropy model can be calibrated by the heterogeneity of a cultural space (differences in the cultural dependence of creators (authors) and “readers” (researchers) of the archaeological complex as a text). When the creator and the “reader” belong to the same culture (the same macrosystem, the same cluster), entropy variation during the same period of time is less than when the creator and the “reader” come from related or different cultures. Another promising direction of research is calculation of entropy for specific complexes of heritage. By this method, we can calculate the entropy of an individual object (e.g. finding), of the whole heritage complex or a subcomplex (e.g. grave) and a complex (e.g. necropolis) relationship. The entropy is calculated using the entropy formula (Голдман, 1957). The resulting entropy is directly (inversely) proportional to the possibilities of the investigator’s ability to understand (“read”) the complex as a text.